FORMULASI DAN UJI KRIM EKSTRAK UMBI SINGKONG (MANIHOT ESCULENTA) TERHADAP LUKA BAKAR PADA KELINCI (ORYCTOLAGUS CUNICULUS) - Rumayar, Inriani MarlinMareyke; Yamlean, Paulina V. Y.; Edy, Hosea Jaya (PHARMACON, 2012)
Crops Cassava (Manihot esculenta) contains carbohydrates, phosphorus, calcium, vitaminC, protein, iron and vitamin B1 can provide a healing effect on wounds. The content contained incassava able to give effect to the skin re-epithelialization of damaged tissues due to burns. Thisstudy aims to determine the effectiveness of the test extract tubers Cassava (Manihot esculenta) inthe dosage form of a cream with the concentration level of 2%, 4%, and 8% for burn woundhealing in rabbits (Oryctolagus cuniculus). Making cream formulation using cassava tuber extractoil phase in water and used as test animals 10 rabbits, divided into 5 treatment groups, namely, testthe cream treatment group, negative control group (basic cream) and a positive control group(Bioplacenton). Burns in the back with a diameter of 1.5 cm were treated and observed the healingeffects for 7 days. The results showed that from day-1 to day-7 observations burns suffereddiminution in diameter. It was concluded that the concentration of 2% cassava extract cream hashealing effect and increasing the concentration of 4% and 8% contained showed more effectiveand speed up the healing process.Keywords: cream, extract, cassava tubers, healing burns, rabbit